MODERN PRIORITIES OF BUILDING PHYSICAL EDUCATION SPECIALISTS’ PROFESSIONAL COMPETENCE: PRACTICALLY ORIENTED VECTOR - Dereka, Тetyana; Tumanova, Valentyna (Continuing Professional Education: Theory and Practice, 2019)
Training programs of physical education specialists’ training, circa 2003, have been analyzed in this article. Elective and normative aspects of physical education specialists’ training curricula have been characterized by training cycles: humanitarian, social-economic, mathematical, of natural studies’, professional and practical (2003, 2008, 2010, 2013, 2015). 2017 curricula of educational programs of professional training, which build general and specific professional competences, have been characterized by clusters of subject areas. Physical education specialists’ training curricula of years 2003, 2008, 2010, 2013, 2015 and 2017 have been characterized by amount of hours and course credits, which are given to academic subjects. Quantity data of students’ teaching and working (both pedagogic and out-of-school) educational practices has been analyzed. Data about physical education specialists’ professional training curricula of years 2003, 2008, 2010, 2013, 2015 and 2017 has been given. Professional competences, which are formed during practically oriented professional training, have been defined, in accordance to modern educational standards and physical education specialists’ professional training curricula. Recommendation documents of the European Comission, requirements of which should be taken into account while formulating new era of higher education standards, have been identified.